You are on page 1of 5

University of Toronto at Scarborough

Division of Computer and Mathematical Sciences,


Mathematics

MAT C46S 2014/15

Problem Set #1
Due date: Wednesday, September 17, 2014 at the beginning of class

PART I
Do the following problems from the text by Shifrin.
Chap. 1.1 question 2, question 8
Solution to Chap. 1.1. question 2:

α(t) = (a cos(t), a sin(t), bt)


α0 (t) = (−a sin(t), a cos(t), b)
|α0 (t)|2 = a2 + b2
Reparametrize α by arc length:
Z t
s(t) = |α0 (u)|2 du
0
Z t
s(t) = (a2 + b2 )dt = (a2 + b2 )(t)
0

s s bs
α(s) = (a cos , a sin 2 , 2 .
(a2 2
+b ) (a + b ) (a + b2 ))
2

Solution to chap 1.1 question 8:


P, Q ∈ R3
α : [a, b] → R3
α(a) = P, α(b) = Q
v =Q−P
Rb
Length of α is a |α0 (t)|dt ≥ Q − P
It is a consequence of Cauchy-Schwarz that
Z b Z b
0
| α (t)dt| ≤ |α0 (t)|dt
a a
1
2

The left hand side is v (because α0 is a total derivative, using the


Fundamental Theorem of Calculus applied to vector-valued functions)
while the right hand side is the length of α. )
Revised solution to Chap 1.2 question 3(e))
Find the Frenet apparatus of the following curve.

α(t) = (cosh t, sinh t, t)


α0 = (sinh t, cosh t, 1)
|α0 (t)|2 = 2 cosh2 (t)

α0 1
0
= √ (s, c, 1)
T =
|α | 2c
here we introduced the notation

c := cosh(t), s := sinh(t).
1 −s
T 0 = √ (c, s, 0) + √ (s, c, 1)
2c 2c2
1
= √ ((c, s, 0) + (− tanh(t))(s, c, 1))
2c
 2
c − s2

0 1
T =√ , 0, − tanh(t)
2c c
1 s2 + 1 1
|T 0 |2 = 2 ( 2 ) = 2
2c c 2c
c2 − s 2
N =( , 0, − tanh(t)).
c
1
B = T × N = √ (−s, 1, −1)
2 2c3
3s 1
B 0 = √ (−s, 1, −1) + √ (−c, 0, 0))
2 2c 4 2 2c3
1
κ = |T 0 | = √
2c
3s 1 s 1 1 1
τ = −B 0 · N = − √ 2
(− + tanh(t)) + √ 3
= √ .
2 2c4 c c 2 2c3 2c 4 2c6
3

Solution to chap 1.1 question 4


|f 00 |
We would like to prove κ = (1+|f 0 |2 )3/2

|α0 × α00 |
κ=
|α0 |3

α(x) = (x, f (x))


α0 = (1, f 0 )
α00 = (0, f 00 )
so
α0 × α00 = f 00 (0, 0, 1)
Also |α0 |2 = 1 + |f 0 |2 This concludes the verification of the above for-
mula.
Solution to Chap. 1.3 question 1(a):
WLOG x = (0, 0, 1) and y = (s, 0, c) .
The arc of the great circle connecting x and y is
(α(t) = (sin u(t) cos v(t), sin u(t) sin v(t), cos u(t))
α0 = (cos(u) cos(v)u0 − sin u sin(v)v 0 , cos(u) sin(v)u0 + sin(u) cos(v)v 0 , cos(u)u0 )
So
|α0 |2 = (cos u cos vu0 −sin u sin vv 0 )2 +(cos u sin vu0 +sin u cos vv 0 )2 +(cos uu0 )2
Z Z
0 2
cos u cos(v)u0 )2 + (sin u sin(v)v 0 )2 − 2 cos(u) sin(u) cos(v) sin(v)u0 v 0

|α | =
Z
cos(u) sin(v)u0 )2 + (sin(u) cos(v)v 0 )2 + 2 cos(u) sin(u) cos(v) sin(v)u0 v 0

+
Z
+ cos2 (u)(u0 )2
Z Z Z
= cos (u)(u ) + sin (u)(v ) + cos2 (u)(u0 )2
2 0 2 2 0 2

(because the two terms with a factor of 2 have cancelled, and we have
used cos2 v +sin2 v = 1). The integral of |α0 |2 is minimized when v 0 = 0,
because each of the three terms in the last integral is positive.
PART II Do the following problem.
1.
4

Find the evolute of the cycloid


x = u + sin(u), y = 1 + cos(u)
(Hint:
T = (cos u/2, − sin(u/2)).

Solution:
x = u + sin(u), y = 1 + cos(u)
x = (u + sin(u), 1 + cos(u))
T is in the direction of
dx du
= (1 + cos(u), − sin(u))
ds ds
2
(2 cos (u/2), −2 sin u/2 cos u/2) · u = 2 cos u/2 · u(cos u/2, − sin u/2)
Since
| (cos u/2, − sin u/2) |= 1
this is the unit in this direction. So
T = (cos u/2, − sin u/2)
1 du
κN = T0 = (− sin u/2, − cos u/2) .
2 ds
Since (− sin u/2, − cos u/2) is a unit vector, we must have N = t(sin u/2, cos u/2)
and
1 du
κ=
2 ds
ds
Hence the radius of curvature is ρ = 2 du , and ρ = 1/κ. Hence
dx dx ds ds
= =T .
du ds du du
So
x0 = (1 + cos u, − sin u)
u
κN = T0 = 2cos T
2
Since (− sin u/2, − cos u/2) is a unit vector, we must have N = −(sin u/2, − cos u/2)
and
dx dx ds ds
= = T
du ds du du
So
ds/duT = (1 + cos u, − sin u) = 2 cos u/2T.
ds
So du = 2 cos u/2. So the radius of curvature is ρ = 4 cos u/2.
5

The position of the centre of curvature is

rc = x + ρN = (u + sin u, 1 + cos u) + 4 cos u/2(− sin u/2, cos u/2)


= (u + sin u, 1 + cos u) − (4 sin u/2 cos u/2, 4 cos2 u/2)
= (u + sin u, 1 + cos u) − (2 sin u, 2 + 2 cos u)
= (u − sin u, −1 − cos u)
The evolute is given by the position of the centre of curvature.
So the equations for the evolute are
x = u − sin u, y = −1 − cos u.
Alternative solution:
Use the following formula for the evolute, denoted x∗ (Schaum’s
Outline p. 86):
Z 
∗ N 1
x =x+ + cot τ ds + c B
κ κ
Note that the original cycloid curve
R x is a plane
 curve, so the torsion τ
is zero and the definite integral τ ds + c is a constant. So the final
answer is
N
x∗ = x +
κ
in agreement with the earlier calculation:
x∗ (u) = (u + sin(u), 1 + cos(u)) − 2(2 sin u/2 cos u/2, 2 cos2 u/2)
= (u − sin(u), −1 − cos(u))